Pengujian Aproksimat Karbon Limbah Sabut Kelapa (Cocos nucifera) - Nanditho Azima Putra; Ananda Putra (Jurnal Periodic Jurusan Kimia UNP, 2023)
The carbon approximation test of coconut coir has been successfully carried out. Carbon made at a temperature of 350 oC with variations in the length of time of 30, 45, 60 and 75 minutes was found to meet the test levels of SNI No. 06-3720-1995 and the best carbonization time for 60 minutes. In coconuts, coconut fiber is the dominating part because almost 35% of the weight of coconuts is coconut husk. The existence of waste is supported by the average production of coconuts in Indonesia of 15.5 billion eggs/year, so that the available material is quite a lot. This is a support in producing carbon because 60% of lignin has a carbon content.